2001
DOI: 10.1097/00002820-200102000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Issues of Women With Breast Cancer

Abstract: This in-depth, qualitative pilot study explored the impact of breast cancer on specific dimensions of the relationships and roles of women. It included interaction within the partner relationship as well as with family, friends, and colleagues. Data were obtained by individual and group interviews from 10 women with a diagnosis of breast cancer and 5 male partners. Both partnered and single women participated. There were four major findings seldom discussed in the literature, which have important implications … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
117
0
11

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(135 citation statements)
references
References 34 publications
7
117
0
11
Order By: Relevance
“…The majority of the participants in this study displayed a clear awareness as to how chemotherapy-induced altered sexuality can adversely impact on relationships and how it can be a genuine concern for women undergoing treatment, supporting existing work (Holmberg et al, 2001). However, all participants in our study considered that dealing with issues around sexuality was a very important aspect of patient care, a finding that is at variance with existing literature that found that nurses did not tend to see sexuality as a component of their nursing care (Williams et al, 1986;Kautz et al 1990).…”
Section: Discussionsupporting
confidence: 79%
“…The majority of the participants in this study displayed a clear awareness as to how chemotherapy-induced altered sexuality can adversely impact on relationships and how it can be a genuine concern for women undergoing treatment, supporting existing work (Holmberg et al, 2001). However, all participants in our study considered that dealing with issues around sexuality was a very important aspect of patient care, a finding that is at variance with existing literature that found that nurses did not tend to see sexuality as a component of their nursing care (Williams et al, 1986;Kautz et al 1990).…”
Section: Discussionsupporting
confidence: 79%
“…From a clinical perspective, the findings underscore the importance of counseling women and their partners about the expected consequences of treatment-related side effects on their intimate relationships. While from a research perspective these results demonstrate the need for additional studies that illuminate how body image and sexual problems are related to each other and affected by interactions between the side effects of breast cancer treatment and pre-existing problems with mental health, self-esteem, and partner relationships (Spencer et al, 1999;Schover, 1991;Holmberg et al, 2001). However, to understand the implications of how the symptoms from the women's initial treatment predict longer-term outcomes is left to longitudinal studies.…”
Section: Discussionmentioning
confidence: 92%
“…In sum, it appears that perceived reactions of the woman's partner represent an important influence on the woman's response to the diagnosis and treatment of this disease (Holmberg et al, 2001;Lyons et al, 1995;Manne, 1998Manne, , 1999Vess, Moreland, Schwebel, & Kraut, 1988;Zunkel, 2002). Given this, it seems important to know more about how partner reactions relate to the patient's emotional, psychosexual, and marital well-being, whether the effect is an adverse one or a beneficial one.…”
mentioning
confidence: 99%